If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(x+4)-6(x-5)=40
We move all terms to the left:
-(x+4)-6(x-5)-(40)=0
We multiply parentheses
-(x+4)-6x+30-40=0
We get rid of parentheses
-x-6x-4+30-40=0
We add all the numbers together, and all the variables
-7x-14=0
We move all terms containing x to the left, all other terms to the right
-7x=14
x=14/-7
x=-2
| X=123x= | | X-(-6)+9+2x-19=23 | | -4|8-5m|=13 | | 5x+3x=7x+6 | | 2(7-7x)=14 | | -41/6=2/3n+11/4n | | -7a+10=-8(a+11) | | 9y4+65y2−144=0 | | 5z-2z=-3 | | (4x/5)+7=6 | | -6+x/6=2 | | 2x+10=3x+65 | | 4(x-7)+6x=32 | | 5(6b-6)-3(b-2)=-51 | | −6x−1+5x^2=8x^2 | | 3x+6-2=-2 | | 2(5+t)=8 | | 74+8x=170 | | -3-3x=7x-123 | | 40x+0.05=15x | | 2.3x-2.3=1.4x-14 | | 8v-2=5+7v | | 1/2x+3=3x-(7-2x) | | 4-(2x-3)-5x=-7 | | 1/3b=b+12 | | 1-3x=2x=8 | | -7-8n=-7(1+6n) | | x+4=2(x+2)-x | | 75+v=245.76 | | 8x+10x^2−6=17x | | (x+1.5)^2=0 | | -3h+13=6(h+2) |